2018
DOI: 10.1292/jvms.18-0074
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals differential gene expression in intramuscular adipose tissues of Jinhua and Landrace pigs

Abstract: Meat is a rich source of protein, fatty acids and carbohydrates for human needs. In addition to necessary nutrients, high fat contents in pork increase the tenderness and juiciness of the meat, featuring diverse application in various dishes. This study investigated the transcriptomic profiles of intramuscular adipose tissues in Jinhua and Landrace pigs by employing advanced RNA sequencing. Results showed significant interesting to note that there were significant differences in the expression of genes. 1,632 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
14
4
Order By: Relevance
“…The majority of adipose transcriptome studies using high-throughput RNA sequencing (RNA-Seq) have been limited to mice [20,21], sheep [22][23][24], pigs [25][26][27], and humans [28][29][30]. Adipose transcriptomes are affected by the type of adipose, as well as by the sex and age of the animal [31].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of adipose transcriptome studies using high-throughput RNA sequencing (RNA-Seq) have been limited to mice [20,21], sheep [22][23][24], pigs [25][26][27], and humans [28][29][30]. Adipose transcriptomes are affected by the type of adipose, as well as by the sex and age of the animal [31].…”
Section: Introductionmentioning
confidence: 99%
“…Current gene annotation based on pig genome build 10.2 is composed of gene identification results from expressed sequence cDNA/tag sequences, bioinformatics prediction, and RNA-seq analyses. Several studies have carried out RNA-seq experiments to profile the transcriptomes of pigs [38,39,40,41]. The present study identified 24,718 expressed transcription units in the subcutaneous adipose tissue of lean (DL) and obese (Min) pig breeds at two different developmental stages (juvenile, 4 weeks old; juvenile-to-adult, 16 weeks old).…”
Section: Discussionmentioning
confidence: 75%
“…CeRNET plays a widely regulatory role in tissue and organ development (Xu et al, 2016;Li et al, 2017;Liu et al, 2018;Miao et al, 2018). To interpret the interplay among diverse RNAs (mRNA, miRNA, and lncRNA) during the antler development, ceRNET was constructed for the first time.…”
Section: Discussionmentioning
confidence: 99%